"Now, What Exactly is the Problem?" Media Coverage of Economic Inequalities and Redistribution Policies: The Piketty Case. Issue 4 (1st October 2020) - Grisold, Andrea; Theine, Hendrik
Abstract: A clear sign of the heightened interest in economic inequality was the surprising popularity of Thomas Piketty's book, Capital in the Twenty‐First Century, presenting a dense synopsis and major contribution to the economics of inequality. This article investigates discourses on inequality in news media, through the highly controversial debate raised by Piketty's best‐selling book, in selected print media in four European countries. We conceive of the media as having an impact on the perceptions and knowledge of economic processes #thus influencing preferences of the public for economic policy making. This is in line with Veblen #who terms the press an "educational system." Regarding the topics of inequality; we will show that media coverage leads to a biased picture of both inequality and the role of redistribution policies to possibly curb such a development